Climacturia After Radical Prostatectomy: MRI-Based Predictors. Issue 9 (18th July 2020) - Sullivan, John F.; Ortega, Yanira; Matsushita, Kazuhito; Choi, Judy M.; Elterman, Dean; Akin, Oguz; Nelson, Christian J.; Sandhu, Jaspreet S.; Mulhall, John P.
Abstract: Background: After radical prostatectomy (RP), climacturia is a prevalent and distressing problem. To date, no specific predictors have been identified. Aim: In this analysis, we sought to find associated pelvic magnetic resonance imaging (MRI) parameters. Methods: We identified all men in our departmental database who (i) had climacturia post-RP, ≥3 episodes; (ii) underwent a pre-RP endorectal MRI; (iii) had no radiation or androgen deprivation therapy (ADT). Soft tissue and bony dimensions were measured by 2 raters blinded to clinical and pathological data. Outcomes: MRI parameters included the following: maximum height, width, and depth of prostate, prostate volume, urethral width and length, lower conjugate of pelvis, bony femoral width, outer and inner levator distances and thickness. Point-biserial correlations were run on univariate associations. Logistic regression was used for the multivariable model. Results: 194 consecutive pre-RP MRI studies were reviewed (56 men with and 138 without climacturia). Mean age was 60 ± 7 years, average time post-RP at assessment, 7 ± 7 months. Of MRI parameters, urethral width (r = 0.13, P = .03) and lower conjugate (r = 0.12, P = .05) were associated with presence of persistent climacturia. 2 others met criteria for multivariable analysis, prostate depth and outer levator distance. Of the non-MRI parameters, none were significantly related to climacturia and only body mass index (BMI) met criteria for multivariable analysis. On multivariable analysis, only urethral width was associated with climacturia (OR = 1.23, 95% CI: 1.01–1.49, P = .04); the wider the urethra, greater the chance of climacturia. Clinical Implications: Improved ability to predict the occurrence of orgasm-associated incontinence in the preoperative setting. Strengths and Limitations: Limitations include the fact that the MRI endorectal probe may have distorted pelvic tissues during imaging and that our study population size was small. However, prospective data collection, blinded measurements by 2 trained readers, and rigorous statistical analysis should be considered strengths. Conclusion: By identifying preoperative risk factors, such as urethral width on MRI, we may be able to better understand the pathophysiology of this condition and furthermore may permit us to better counsel men regarding this postoperative outcome.